O-022 Perfusion-based selection leads to improved outcomes compared with time-based selection for endovascular reperfusion therapy in acute ischaemic stroke. (14th July 2013) - Soltanolkotabi, M; Prabhakaran, S; Shaibani, A; Hurley, M; Curran, Y; Conners, J; Lee, V; Ansari, S
Abstract : Background: Controversy exists on the role of perfusion imaging-based selection of patients with acute ischaemic stroke (AIS) for endovascular reperfusion therapy (ERT). Our hypothesis was that perfusion imaging based selection would improve functional outcomes at 3 months compared to time based selection alone. Methods: We reviewed data from consecutive AIS patients treated with ERT at 4 centres between 2006 and 2011. We excluded patients with initial NIHSS score < 8 and those with posterior circulation occlusions. We collected data on demographics, initial NIHSS score, intravenous tissue plasminogen activator (IV tPA), use of perfusion imaging (CT or MRI), time from onset to groin puncture, initial and final reperfusion grade using the modified TICI scale, procedural complications using ECASS criteria, and functional outcome defined as modified Rankin Scale (mRS) 0–2 at 3 months. Using univariable statistics and multivariable logistic regression, we assessed whether patients who underwent perfusion imaging had better outcomes than those selected based on time alone. We estimated odds ratios (OR) and 95% confidence intervals (CI) in the final model. Results: One-hundred eighty-five patients (mean age 66.7 years; median NIHSS score 19; MCA occlusion 73% and ICA occlusion 27%) were included. TICI 2b or 3 reperfusion grade was achieved in 49.7% while symptomatic haemorrhage (PH1, PH2, or perforation) occurred in 10.8%. Good outcome at 3 months was seen in 41.7%. Perfusion imaging was used in 69 (37.3%) patients (45 CT and 24 MRI) and was associated with increased onset-to-groin puncture time (359 vs 298 minutes, P=0.019). Patients who underwent perfusion imaging were also older (73 vs 63 years, P<0.001). Those who underwent perfusion imaging were more likely to have good outcome (53.6 vs 34.5%, P=0.011). In multivariable analysis, perfusion imaging remained a predictor of good outcome (adj. OR 2.35, 95% CI 1.17-4.72), independent of initial NIHSS score (adj. OR 0.91, 95% CI 0.86-0.97), TICI 2b or 3 reperfusion (adj. OR 4.94, 95 CI 2.50-9.76), and IV tPA use (adj. OR 2.50, 95% CI 1.26-4.94). Conclusions: In this multi-centre study, AIS patients who underwent perfusion imaging were over 2-fold more likely to have good outcome following ERT despite a delay in time to treatment and age imbalance between groups. Further studies should continue to address the optimal perfusion imaging thresholds for patient selection for ERT. Disclosures: M. Soltanolkotabi: None. S. Prabhakaran: None. A. Shaibani: None. M. Hurley: None. Y. Curran: None. J. Conners: None. V. Lee: None. S. Ansari: None.